Qur'anic Values in the Luberan Tradition: Strengthening Religious Moderation Based on Local Wisdom - Albab, Ulul; Riandita, Lilik; Mutammam, Mutammam; Fanany, Rebecca; Ana, Nurlaila; Ta'rifin, Ahmad (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2023)
This study examines the harmony of the